EFEKTIFITAS PAKET ASI (EDUKASI KESEHATAN : LAKTASI DAN PIJAT OKSITOSIN) TERHADAP PRODUKSI ASI IBU PRIMIPARA - Ulva Noviana (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2018)
Breast Milk (ASI) is the most perfectfood for the baby, where the nutritional contentin accordance with the need for intelligence.Breast milk contains antibody substances thatare useful for preventing infectious boweldisease and optimal digestion of growth anddevelopment. Based on the preliminary study ofNovember 2017 on 10 primiparous postpartumwomen, there were 7 postpartum mothersproducing less milk. The objectives of the studyanalyzed the differences in breast milkproduction in postpartum women before andafter being given a successful breastfeedingpackageThis study used pre experimental designwith one group pretest postest model ofindependent variables Package "Sukses ASI" andthe dependent variable was milk production. Thepopulation of this study were 20 primiparouspostpartum women and the samples were 19primiparous mothers using random samplingtechnique.The results showed that most of theAsylum production mothers were less thanbefore the "Successful Breastfeeding" packagewith mean of 4.21 and most of Asi's postpartummothers were fluent after being given the"Successful Breastfeeding" package with meanof 7.89. Based on statistical test with paired ttest obtained p value = 0.000, where this value issmaller than alpha 0,05 so H1 was accepted,meaning that there was difference of milkproduction before and after given packet ofsuccess of ASIIt is expected to provide inputs forhealth workers to increase breastfeedingproduction in primiparous postpartum mothers.This package will be more effective if the deliveryof health education not only with edge leafleatby using video. For the people of this "SuccessfulBreastfeeding" package people can becomeaware of the importance of breastfeeding